Genetic tagging of the adenosine A2A receptor reveals its heterogeneous expression in brain regions - Wang, Muran; Li, Zewen; Song, Yue; Sun, Qiuqin; Deng, Lu; Lin, Zhiqing; Zeng, Yang; Qiu, Chunhong; Lin, Jingjing; Guo, Hui; Chen, Jiangfan; Guo, Wei (Frontiers in Neuroanatomy, 2022)
The adenosine A2A receptor (A2AR), a G protein-coupled receptor, is involved in numerous and varied physiological and pathological processes, including inflammation, immune responses, blood flow, and neurotransmission. Accordingly, it has become an important drug target for the treatment of neuropsychiatric disorders. However, the exact brain distribution of A2AR in regions outside the striatum that display relatively low levels of endogenous A2AR expression has hampered the exploration of A2AR functions under both physiological and pathological conditions. To further study the detailed distribution of the A2AR in low-expression regions, we have generated A2AR knock-in mice in which the 3xHA-2xMyc epitope tag sequence was fused to the C-terminus of A2AR (A2AR-tag mice) via CRISPR/Cas9 technology. Here, using CRISPR/Cas9 technology, we have generated A2AR knock-in mice in which the 3xHA-2xMyc epitope tag sequence was fused to the C-terminus of A2AR (A2AR-tag mice). The A2AR-tag mice exhibited normal locomotor activity and emotional state. Consistent with previous studies, A2AR fluorescence was widely detected in the striatum, nucleus accumbens, and olfactory tubercles, with numerous labeled cells being evident in these regions in the A2AR-tag mouse. Importantly, we also identified the presence of a few but clearly labeled cells in heterogeneous brain regions where A2AR expression has not previously been unambiguously detected, including the lateral septum, hippocampus, amygdala, cerebral cortex, and gigantocellular reticular nucleus. The A2AR-tag mouse represents a novel useful genetic tool for monitoring the expression of A2AR and dissecting its functions in brain regions other than the striatum.